From Silk Spinning to 3D Printing: Polymer Manufacturing using Directed Hierarchical Molecular Assembly. Issue 15 (28th February 2020) - Mu, Xuan; Fitzpatrick, Vincent; Kaplan, David L.
Abstract: Silk spinning offers an evolution‐based manufacturing strategy for industrial polymer manufacturing, yet remains largely inaccessible as the manufacturing mechanisms in biological and synthetic systems, especially at the molecular level, are fundamentally different. The appealing characteristics of silk spinning include the sustainable sourcing of the protein material, the all‐aqueous processing into fibers, and the unique material properties of silks in various formats. Substantial progress has been made to mimic silk spinning in artificial manufacturing processes, despite the gap between natural and artificial systems. This report emphasizes the universal spinning conditions utilized by both spiders and silkworms to generate silk fibers in nature, as a scientific and technical framework for directing molecular assembly into high‐performance structures. The preparation of regenerated silk feedstocks and mimicking native spinning conditions in artificial manufacturing are discussed, as is progress and challenges in fiber spinning and 3D printing of silk‐composites. Silk spinning is a biomimetic model for advanced and sustainable artificial polymer manufacturing, offering benefits in biomedical applications for tissue scaffolds and implantable devices. Abstract : Silk spinning by both silkworms and spiders embodies a "living" and largely inaccessible nanotechnology for manufacturing strong materials with eco‐friendly and energy‐minimum processing conditions. To fully unleash the potential of the silk spinning requires continuous biomimetic efforts, which, notably, is beyond the scope of the mere reconstruction of natural hierarchical structures of silks.